Application of Mathematics Tree Learning Media to Improve Mathematics Learning Outcomes in Class VIIa Students of SMP Negeri 3 Bontonompo - Purnama, Firda Hadi; Yuliany, Nur; Mattoliang, Lisnasari Andi; Sriyanti, A.; Baharuddin, (Alauddin Journal of Mathematics Education, 2023)
This research is Classroom Action Research (PTK) or Classroom Action Research (CAR), which aims to improve mathematics learning outcomes for class VIIa students at SMP Negeri 3 Bontonompo by applying the mathematics tree learning media. The subjects of this research were class VIIa students at SMP Negeri 3 Bontonompo, with a total of 32 students, consisting of 16 male and 16 female students. This research was carried out in 2 cycles, and each cycle was carried out in 5 meetings, including a test at the end of each cycle. Data collection was carried out using student learning outcomes tests at the end of each cycle, and observations were carried out every time the learning process took place. The collected data was analyzed using quantitative analysis and qualitative analysis. The results achieved after implementing learning actions using the mathematics tree learning media for two cycles were an increase in students' mathematics learning outcomes. This can be seen from the average score of the test results: in cycle I, it was 69 in the high category, increasing in cycle II to 80 in the very high category. According to the observation sheet carried out during the research, there was an increase in students' activeness and activity in the teaching and learning process. Learning using the mathematics tree learning media can create interesting, fun, and meaningful learning situations for students. From the analysis results, it can be concluded that applying the mathematics tree learning media can improve mathematics learning outcomes for class VIIa students at SMP Negeri 3 Bontonompo.